UV adhesive, UV adhesive film and preparation method thereof
By adding benzophenone monomers and tris(trimethylsiloxy)silyl monomers to UV glue, the cohesive strength and flexibility of UV glue are synergistically improved, and the problem of existing UV glues is difficult to take into account low UV viscosity increase, high UV viscosity reduction and low residual glue amount, achieving excellent viscosity reduction effects and extremely low residual glue amount.
Patent Information
- Application Number
- CN202510043655.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The existing UV viscosity-reducing glue is difficult to take into account the problems of low UV viscosity increase, high UV viscosity reduction and low residual glue amount.
By simultaneously adding benzophenone monomers of specific molecular weights and tris(trimethylsiloxy)silyl monomers to the UV glue, synergistically improves the cohesive strength and dynamic flexibility of the UV glue, and reduces the peeling force and residual glue amount.
The high peeling strength of UV glue before UV irradiation is achieved, and the viscosity-enhancing effect is significant after low UV dose irradiation, and the viscosity-reducing effect is good after high UV dose irradiation, and the residual glue amount is significantly reduced.
Smart Images

Figure BDA0005237683200000041 
Figure BDA0005237683200000141 
Figure BDA0005237683200000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer optical adhesives, and in particular to UV adhesive, UV adhesive film and a preparation method thereof. Background Art
[0002] With the rapid development and rise of the semiconductor industry, the demand for glue in the semiconductor wafer field has also grown rapidly. UV anti-sticking adhesive film is needed to fix and protect the wafer during wafer cutting and grinding. The UV anti-sticking adhesive used for wafer cutting is an adhesive that can provide high adhesion under normal conditions and whose adhesion drops sharply after UV irradiation. Before UV irradiation, the anti-sticking adhesive film fixes the wafer through high adhesion to prevent the silicon wafer from cracking during the cutting process; after the cutting is completed, the anti-sticking adhesive loses its viscosity after UV irradiation, making it easier to pick up the wafer. In recent years, with the development of the electronic information industry, semiconductor electronic devices have become thinner and thinner, making wafers more easily damaged during processing. Therefore, while requiring UV anti-sticking adhesive to have high normal adhesion, higher requirements are placed on the residual glue amount and anti-sticking property of the UV anti-sticking adhesive after curing.
[0003] At present, some researchers have reduced the amount of residual glue by changing the existing viscosity-reducing adhesive system. The designed UV viscosity-reducing adhesive system includes acrylate copolymer base glue, bifunctional polyurethane prepolymer, cross-linking agent, photoinitiator and dispersant and other additives. The polyurethane prepolymer with isocyanate terminal group can undergo cross-linking reaction with acrylate copolymer base glue containing hydroxyl and carboxyl groups to form a network structure, and then form an interpenetrating network structure with the polymer network generated after UV irradiation. Compared with the semi-interpenetrating network structure, the network is denser and the peeling performance is better. However, experiments have found that the peeling strength of the viscosity-reducing adhesive is still very high after UV irradiation, and the residues of the cleavage-type small molecule photoinitiator used are easy to migrate to the wafer surface and form residual glue; some researchers have also designed terminal hydroxyl fumaryl chloride-pentanediol copolyester, isophorone diisocyanate, chain extender, free radical small molecule photoinitiator as The viscosity-reducing adhesive system has a 180° peel strength of 19N / 25mm before light curing and a 180° peel strength of 0.4N / 25mm after light curing. However, since it is a multi-component compound, compatibility problems will occur, resulting in large fluctuations in peel strength before UV irradiation. At the same time, the small molecule photoinitiator is free in the system and easily migrates to the surface of the adhesive layer to produce residual adhesive. Moreover, since the cohesive strength of the adhesive layer is greatly increased after curing, the maximum peel strength during the peeling process is high, causing the wafer to break and reducing the yield rate. The existing UV viscosity-reducing adhesive also includes a viscosity-reducing adhesive system compounded with acrylate copolymer base glue, multifunctional polyurethane prepolymer, photoinitiator, functional diluent and other auxiliary agents. The UV viscosity-reducing adhesive composition has low adhesion and low peeling force after UV irradiation, but due to its complex composition and poor compatibility of each component, components are separated, resulting in short storage life and other problems. Therefore, it is urgent to study a new UV adhesive to solve the problem that the existing UV adhesive cannot take into account low UV viscosity increase, high UV viscosity reduction and low residual adhesive. Summary of the invention
[0004] In view of the above problems, the present invention provides a UV adhesive, a UV adhesive film and a preparation method thereof.
[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0006] The first aspect of the present invention provides a UV adhesive, comprising the following raw material components in parts by weight: 43-47 parts of isooctyl acrylate, 10-13 parts of butyl acrylate, 2-3 parts of hydroxyethyl acrylate, 4-5 parts of methyl methacrylate, 1-2 parts of acrylic acid, 2-4 parts of benzophenone monomers and 1-7 parts of tris(trimethylsiloxy)silyl monomers;
[0007] Wherein, the molecular weight of the benzophenone monomer is 200-300;
[0008] The molecular weight of the tris(trimethylsiloxy)silyl monomer is 370-470.
[0009] At present, when preparing traditional UV viscosity-reducing adhesives, the adhesive is mainly increased and reduced in viscosity through the thermal curing reaction between the active groups of the thermal curing agent (such as isocyanate and epoxy groups) and the functional groups (such as hydroxyl and carboxyl groups) in the main acrylic copolymer adhesive. On the one hand, the operation steps are complicated, the curing temperature is high, and the energy consumption is high. On the other hand, the small molecules such as the thermal curing agent used are difficult to react completely, and the residues are easy to migrate to the surface of the wafer to form residual adhesive. Therefore, in view of the problems of the complex composition of the existing UV adhesive system, poor compatibility of the components, and a large amount of peeled residual adhesive, it is urgent to provide a UV adhesive.
[0010] Although the UV viscosity-reducing adhesive bonded only with benzophenone monomers has a self-increasing and viscosity-reducing effect after UV irradiation, the initial peeling strength of the adhesive is low due to the insufficient internal polymerization strength of the viscosity-reducing adhesive, and the UV viscosity-increasing and viscosity-reducing effect is not obvious, and residual adhesive is easily caused. The inventor accidentally discovered through a large number of experiments that by adding benzophenone monomers and tris(trimethylsiloxy)silyl monomers of a specific molecular weight to the UV adhesive at the same time, the tris(trimethylsiloxy)silyl monomer can effectively make up for the disadvantage of low cohesive strength of benzophenone monomers, and improve the cohesive strength of UV adhesive to a certain extent. In addition, the Si-O-Si bond in the tris(trimethylsiloxy)silyl monomer can make the UV adhesive have higher dynamic flexibility and reduce the intermolecular force in the system. It synergizes with the benzophenone monomer to reduce the surface tension and surface energy of the prepared UV adhesive during peeling, effectively reducing the peeling force during the peeling process and significantly reducing the amount of residual adhesive. The UV glue provided by the present invention has simple components, and the viscosity increase and viscosity reduction of the UV glue can be conveniently achieved by controlling the UV irradiation dose, without the need to add additional ingredients such as thermal curing agents and photopolymerization components, thereby solving the problem of poor compatibility of existing UV glue systems, not only facilitating uniform coating, but also fundamentally solving the problem of residual glue.
[0011] The inventors have proved through a large number of experiments that when the amount of benzophenone monomers is too high, the molecular weight of the UV glue is too large, which makes the molecular chain rigidity of the UV glue too large, resulting in low peel strength before UV irradiation; when the amount of benzophenone monomers is too small, the cross-linking sites of the UV glue copolymer are too few, and the viscosity reduction effect after UV irradiation is poor. When the amount of tris(trimethylsiloxy)silyl monomers is too low, the cohesive strength of the copolymer is significantly low, resulting in low peel strength of the UV glue before UV irradiation; when the amount of tris(trimethylsiloxy)silyl monomers is too high, the molecular weight of the UV glue copolymer is too large, the rigidity is too high, the surface wetting ability of the UV glue is poor, and the coating is difficult.
[0012] The present invention further controls the amount of benzophenone monomers and tris(trimethylsiloxy)silyl monomers added to make the UV adhesive have a suitable molecular weight, flexibility and intermolecular chain interaction force, which is conducive to the synergistic effect of benzophenone monomers and tris(trimethylsiloxy)silyl monomers, so that the UV adhesive has excellent viscosity increase and decrease effects and very little residual adhesive, achieving low UV viscosity increase, high UV viscosity reduction and low residual adhesive. The UV adhesive provided by the present invention has a 180° peel strength of 20N / 25mm-40N / 25mm before UV irradiation, and after a low UV dose (5mJ / cm 2 -30mJ / cm 2 ) irradiation, UV adhesive can achieve adhesion enhancement effect, 180° peel strength can be increased to 26N / 25mm-43N / 25mm; after high UV dose (30000mJ / cm 2 -40000mJ / cm 2 ) after irradiation, the crosslinking degree of the UV glue polymer is greatly increased, achieving a viscosity reduction effect, and the 180° peel strength can be reduced to 0.12N / 25mm-0.35N / 25mm. In addition, the water contact angle of the substrate after peeling off the UV glue can be as low as 74.71°, which is close to the water contact angle of the blank substrate (72.68°). The UV glue provided by the present invention also has an extremely low amount of residual glue.
[0013] Preferably, the benzophenone monomer is 4-acryloxybenzophenone.
[0014] Preferably, the tris(trimethylsiloxy)silane-based monomer is 3-methacryloxypropyltris(trimethylsiloxy)silane.
[0015] The structural formula of the UV glue provided by the present invention is:
[0016]
[0017] The present invention further defines the specific substances of benzophenone monomers and tris(trimethylsiloxy)silyl monomers, which can make the UV adhesive form a specific structure, so that the UV adhesive has the advantages of excellent viscosity increase and decrease effect and very little residual adhesive.
[0018] The second aspect of the present invention provides a method for preparing UV glue, comprising the following steps:
[0019] S1, isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, acrylic acid, benzophenone monomers and tris(trimethylsiloxy)silyl monomers are mixed uniformly to obtain a polymer mixed solution;
[0020] S2, mixing benzoyl peroxide, anhydrous ethanol and ethyl acetate uniformly to obtain an initiator solution;
[0021] S3, mixing the polymer mixed solution and the initiator solution uniformly to obtain a mixed solution;
[0022] S4, reacting 33wt%-50wt% of the total amount of the mixed solution at 73° C.-76° C. to obtain a first reactant;
[0023] S5. Add the remaining mixed solution to the first reactant, and then react at 73° C.-76° C. to obtain UV glue.
[0024] Compared with the prior art, the preparation method provided by the present invention only requires the addition of an initiator to polymerize the raw material components of the UV glue, without the need for complicated synthesis steps and operating equipment. The preparation process is green and environmentally friendly, and is easy to realize industrial production, thereby reducing the production cost to a certain extent. Moreover, the preparation method provided by the present invention only requires strict control of the mass ratio of the monomers, the selection of the initiator, and the reaction conditions, so as to stably prepare consistent UV glue products, thereby ensuring the stability and reliability of the product quality, and facilitating large-scale production and quality control.
[0025] Preferably, in S2, the mass ratio of benzoyl peroxide, anhydrous ethanol and ethyl acetate is (1-2):(13-15):(13-15).
[0026] Preferably, in S3, the mass ratio of the polymer mixed solution to the initiator solution is (70-73):(27-32).
[0027] Preferably, the present invention is conducive to further improving the viscosity increase and decrease effect of UV adhesive and reducing the amount of residual adhesive during peeling by limiting the specific ratio of the initiator and the initiator solution and the polymer mixed solution.
[0028] Preferably, in S4, the reaction time is 0.5h-1h.
[0029] Preferably, in S5, the remaining mixed solution is added dropwise at a uniform speed for a time of 0.5 h to 1 h.
[0030] By controlling the time for the uniform dripping to be completed, it is beneficial to control the reaction rate and the molecular weight and distribution of the product, thereby further improving the performance of the UV glue.
[0031] Preferably, in S5, the condition for the reaction to end is: the viscosity of the reactants is 50000 mPa·s-200000 mPa·s.
[0032] Preferably, in S5, after the reaction is completed, it is necessary to evaporate excess solvent.
[0033] The third aspect of the present invention provides a UV adhesive film, comprising a base film layer, a UV adhesive layer and a release film layer stacked in sequence;
[0034] The UV adhesive layer is prepared from the UV adhesive.
[0035] Preferably, the base film layer is made of polyolefin or polyester.
[0036] Preferably, the base film layer has a thickness of 80 μm-120 μm.
[0037] Preferably, the thickness of the UV adhesive layer is 28 μm-32 μm.
[0038] Preferably, the release film layer is made of polyester or polyolefin.
[0039] Preferably, the release film layer has a thickness of 20 μm-50 μm.
[0040] A fourth aspect of the present invention provides a method for preparing a UV adhesive film, comprising the following steps:
[0041] Step 1, mixing the UV glue and ethyl acetate evenly to obtain a UV glue solution with a solid content of 45%-55%;
[0042] Step 2, coating the UV adhesive solution on the base film layer and drying to obtain a composite layer;
[0043] Step 3: UV irradiate the composite layer, attach a release film layer, and age it to obtain a UV adhesive film.
[0044] Preferably, in step 2, the base film layer also needs corona treatment.
[0045] Preferably, in step 2, the drying conditions are: temperature of 78° C.-80° C., and time of 2.5 min-3 min.
[0046] Preferably, in step 3, the wavelength of UV during UV irradiation is 365nm and the dose of UV is 5mJ / cm 2 -30mJ / cm 2 .
[0047] Preferably, in step 3, the aging conditions are: temperature 34° C.-36° C., humidity 59%-61%, and time 23h-25h. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0049] In order to better illustrate the present invention, further examples are given below.
[0050] Example 1
[0051] This embodiment provides a UV adhesive, comprising the following raw material components in parts by weight: 45 parts of isooctyl acrylate, 11 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, 5 parts of methyl methacrylate, 2 parts of acrylic acid, 2 parts of 4-acryloxybenzophenone and 2 parts of 3-methacryloxypropyl tris(trimethylsiloxy)silane;
[0052] This embodiment also provides a method for preparing the above-mentioned UV glue, comprising the following steps:
[0053] S1. Evenly mix the weighed isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, acrylic acid, 4-acryloxybenzophenone and 3-methacryloxypropyltris(trimethylsiloxy)silane to obtain a polymer mixed solution;
[0054] S2, mixing benzoyl peroxide, anhydrous ethanol and ethyl acetate uniformly to obtain an initiator solution, wherein the mass ratio of benzoyl peroxide, anhydrous ethanol and ethyl acetate is 1:14:14;
[0055] S3, mixing the polymer mixed solution and the initiator solution uniformly to obtain a mixed solution, wherein the mass ratio of the polymer mixed solution to the initiator solution is 70:29;
[0056] S4, adding 50 wt % of the mixed solution into the reactor at 75° C. and reacting for 0.5 h to obtain a first reactant;
[0057] S5. uniformly add the remaining mixed solution to the first reactant, control the uniform addition time to be completed to be 1 hour, then react at 75°C until the viscosity of the reactant reaches 50000 mPa·s, stop the reaction, evaporate the solvent, and obtain UV glue.
[0058] Example 2
[0059] The present embodiment provides a UV adhesive, comprising the following raw material components in parts by weight: 45 parts of isooctyl acrylate, 11 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, 5 parts of methyl methacrylate, 2 parts of acrylic acid, 3 parts of 4-acryloxybenzophenone and 2 parts of 3-methacryloxypropyl tris(trimethylsiloxy)silane;
[0060] This embodiment also provides a method for preparing the above-mentioned UV glue, comprising the following steps:
[0061] S1. Evenly mix the weighed isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, acrylic acid, 4-acryloxybenzophenone and 3-methacryloxypropyltris(trimethylsiloxy)silane to obtain a polymer mixed solution;
[0062] S2, mixing benzoyl peroxide, anhydrous ethanol and ethyl acetate uniformly to obtain an initiator solution, wherein the mass ratio of benzoyl peroxide, anhydrous ethanol and ethyl acetate is 2:15:15;
[0063] S3, mixing the polymer mixed solution and the initiator solution uniformly to obtain a mixed solution, wherein the mass ratio of the polymer mixed solution to the initiator solution is 71:32;
[0064] S4, adding 33 wt % of the mixed solution into the reactor at 73° C. and reacting for 1 h to obtain a first reactant;
[0065] S5. uniformly add the remaining mixed solution to the first reactant, control the uniform addition time to be completed to be 0.5 h, then react at 76° C. until the viscosity of the reactant reaches 80000 mPa·s, stop the reaction, evaporate the solvent, and obtain UV glue.
[0066] Example 3
[0067] The present embodiment provides a UV adhesive, comprising the following raw material components in parts by weight: 45 parts of isooctyl acrylate, 11 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, 5 parts of methyl methacrylate, 2 parts of acrylic acid, 4 parts of 4-acryloxybenzophenone and 2 parts of 3-methacryloxypropyl tris(trimethylsiloxy)silane;
[0068] This embodiment also provides a method for preparing the above-mentioned UV glue, comprising the following steps:
[0069] S1. Evenly mix the weighed isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, acrylic acid, 4-acryloxybenzophenone and 3-methacryloxypropyltris(trimethylsiloxy)silane to obtain a polymer mixed solution;
[0070] S2, mixing benzoyl peroxide, anhydrous ethanol and ethyl acetate uniformly to obtain an initiator solution, wherein the mass ratio of benzoyl peroxide, anhydrous ethanol and ethyl acetate is 1:14:15;
[0071] S3, mixing the polymer mixed solution and the initiator solution uniformly to obtain a mixed solution, wherein the mass ratio of the polymer mixed solution to the initiator solution is 72:30;
[0072] S4, adding 40 wt % of the mixed solution into the reactor at 76° C. and reacting for 0.7 h to obtain a first reactant;
[0073] S5. uniformly add the remaining mixed solution to the first reactant, control the uniform addition time to be completed to be 0.6h, then react at 73°C until the viscosity of the reactant reaches 120000mPa·s, stop the reaction, evaporate the solvent, and obtain UV glue.
[0074] Example 4
[0075] This embodiment provides a UV adhesive, comprising the following raw material components in parts by weight: 46 parts of isooctyl acrylate, 12 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, 5 parts of methyl methacrylate, 2 parts of acrylic acid, 2 parts of 4-acryloxybenzophenone and 1 part of 3-methacryloxypropyl tris(trimethylsiloxy)silane;
[0076] This embodiment also provides a method for preparing the above-mentioned UV glue, comprising the following steps:
[0077] S1. Evenly mix the weighed isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, acrylic acid, 4-acryloxybenzophenone and 3-methacryloxypropyltris(trimethylsiloxy)silane to obtain a polymer mixed solution;
[0078] S2, mixing benzoyl peroxide, anhydrous ethanol and ethyl acetate uniformly to obtain an initiator solution, wherein the mass ratio of benzoyl peroxide, anhydrous ethanol and ethyl acetate is 1:14:14;
[0079] S3, mixing the polymer mixed solution and the initiator solution uniformly to obtain a mixed solution, wherein the mass ratio of the polymer mixed solution to the initiator solution is 71:29;
[0080] S4, adding 50 wt % of the mixed solution into the reactor at 75° C. and reacting for 0.5 h to obtain a first reactant;
[0081] S5. uniformly add the remaining mixed solution to the first reactant, control the uniform addition time to be completed to be 1 hour, then react at 75°C until the viscosity of the reactant reaches 50000 mPa·s, stop the reaction, evaporate the solvent, and obtain UV glue.
[0082] Example 5
[0083] This embodiment provides a UV adhesive, comprising the following raw material components in parts by weight: 44 parts of isooctyl acrylate, 11 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, 5 parts of methyl methacrylate, 2 parts of acrylic acid, 2 parts of 4-acryloxybenzophenone and 4 parts of 3-methacryloxypropyl tris(trimethylsiloxy)silane;
[0084] This embodiment also provides a method for preparing the above-mentioned UV glue, comprising the following steps:
[0085] S1. Evenly mix the weighed isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, acrylic acid, 4-acryloxybenzophenone and 3-methacryloxypropyltris(trimethylsiloxy)silane to obtain a polymer mixed solution;
[0086] S2, mixing benzoyl peroxide, anhydrous ethanol and ethyl acetate uniformly to obtain an initiator solution, wherein the mass ratio of benzoyl peroxide, anhydrous ethanol and ethyl acetate is 1:14:14;
[0087] S3, mixing the polymer mixed solution and the initiator solution uniformly to obtain a mixed solution, wherein the mass ratio of the polymer mixed solution to the initiator solution is 71:29;
[0088] S4, adding 50 wt % of the mixed solution into the reactor at 75° C. and reacting for 0.5 h to obtain a first reactant;
[0089] S5. uniformly add the remaining mixed solution to the first reactant, control the uniform addition time to be completed to be 1 hour, then react at 75°C until the viscosity of the reactant reaches 120000 mPa·s, stop the reaction, evaporate the solvent, and obtain UV glue.
[0090] Example 6
[0091] This embodiment provides a UV adhesive, comprising the following raw material components in parts by weight: 43 parts of isooctyl acrylate, 11 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, 5 parts of methyl methacrylate, 2 parts of acrylic acid, 2 parts of 4-acryloxybenzophenone and 7 parts of 3-methacryloxypropyl tris(trimethylsiloxy)silane;
[0092] This embodiment also provides a method for preparing the above-mentioned UV glue, comprising the following steps:
[0093] S1. Evenly mix the weighed isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, acrylic acid, 4-acryloxybenzophenone and 3-methacryloxypropyltris(trimethylsiloxy)silane to obtain a polymer mixed solution;
[0094] S2, mixing benzoyl peroxide, anhydrous ethanol and ethyl acetate uniformly to obtain an initiator solution, wherein the mass ratio of benzoyl peroxide, anhydrous ethanol and ethyl acetate is 2:15:15;
[0095] S3, mixing the polymer mixed solution and the initiator solution uniformly to obtain a mixed solution, wherein the mass ratio of the polymer mixed solution to the initiator solution is 73:32;
[0096] S4, adding 50 wt % of the mixed solution into the reactor at 75° C. and reacting for 0.5 h to obtain a first reactant;
[0097] S5. uniformly add the remaining mixed solution to the first reactant, control the uniform addition time to be completed to be 1 hour, then react at 75°C until the viscosity of the reactant reaches 200000 mPa·s, stop the reaction, evaporate the solvent, and obtain UV glue.
[0098] Comparative Example 1
[0099] This comparative example provides a UV adhesive, which is different from Example 1 in that: the amount of 4-acryloxybenzophenone is increased, specifically, the raw material components include the following parts by weight: 45 parts of isooctyl acrylate, 11 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, 5 parts of methyl methacrylate, 2 parts of acrylic acid, 6 parts of 4-acryloxybenzophenone and 2 parts of 3-methacryloxypropyl tris(trimethylsiloxy)silane;
[0100] The other operations are the same as those in Example 1.
[0101] Comparative Example 2
[0102] This comparative example provides a UV adhesive, which is different from Example 1 in that: the amount of 4-acryloxybenzophenone is reduced, specifically, the raw material components include the following parts by weight: 45 parts of isooctyl acrylate, 11 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, 5 parts of methyl methacrylate, 2 parts of acrylic acid, 1.5 parts of 4-acryloxybenzophenone and 2 parts of 3-methacryloxypropyl tris(trimethylsiloxy)silane;
[0103] The other operations are the same as those in Example 1.
[0104] Comparative Example 3
[0105] This comparative example provides a UV adhesive, which is different from Example 1 in that: the amount of 3-methacryloxypropyl tris(trimethylsiloxy)silane is reduced, specifically, the raw material components include the following parts by weight: 45 parts of isooctyl acrylate, 11 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, 5 parts of methyl methacrylate, 2 parts of acrylic acid, 2 parts of 4-acryloxybenzophenone and 0.5 parts of 3-methacryloxypropyl tris(trimethylsiloxy)silane;
[0106] The other operations are the same as those in Example 1.
[0107] Comparative Example 4
[0108] This comparative example provides a UV adhesive, which is different from Example 1 in that: the amount of 3-methacryloxypropyl tris(trimethylsiloxy)silane is increased, specifically, the raw material components include the following parts by weight: 45 parts of isooctyl acrylate, 11 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, 5 parts of methyl methacrylate, 2 parts of acrylic acid, 2 parts of 4-acryloxybenzophenone and 8 parts of 3-methacryloxypropyl tris(trimethylsiloxy)silane;
[0109] The other operations are the same as those in Example 1.
[0110] Result: The colloid was too hard to be removed.
[0111] Comparative Example 5
[0112] This comparative example is different from Example 1 in that: 3-methacryloxypropyl tris(trimethylsiloxy)silane is replaced with an equal amount of 3-methacryloxypropyl methyldimethoxysilane;
[0113] The other operations are the same as those in Example 1.
[0114] Result: After the remaining mixed solution was added to S5, it exploded and could not react normally.
[0115] Comparative Example 6
[0116] This comparative example is different from Example 1 in that 3-methacryloxypropyl tris(trimethylsiloxy)silane is replaced with an equal amount of methacryloxypropylmethyldiethoxysilane;
[0117] The other operations are the same as those in Example 1.
[0118] Result: After the remaining mixed solution was added to S5, it exploded and could not react normally.
[0119] Comparative Example 7
[0120] This comparative example provides a UV adhesive, which is different from Example 1 in that: 4-acryloxybenzophenone is replaced with an equal amount of benzophenone;
[0121] The other operations are the same as those in Example 1.
[0122] Comparative Example 8
[0123] This comparative example provides a UV glue, including the following preparation method:
[0124] 1. Under nitrogen atmosphere, 32 parts of castor oil, 21 parts of isophorone diisocyanate, 1 part of dibutyltin dilaurate and 25 parts of ethyl acetate were placed in a four-necked bottle, stirred and reacted at 60°C for 6 hours, 20 parts of pentaerythritol triacrylate and 1 part of p-tert-butylcatechol were added, and the NCO content of the reactants was measured every 0.5 hours. When the designed value was reached, the reaction was stopped to obtain a castor oil-based polyurethane prepolymer;
[0125] 2. Evenly mix 45 parts of isooctyl acrylate, 11 parts of butyl acrylate, 3 parts of hydroxyethyl acrylate, 5 parts of methyl methacrylate, 2 parts of acrylic acid and 2 parts of 4-acryloxybenzophenone to obtain a polymer mixed solution;
[0126] 3. Evenly mix benzoyl peroxide, anhydrous ethanol and ethyl acetate to obtain an initiator solution, wherein the mass ratio of benzoyl peroxide, anhydrous ethanol and ethyl acetate is 1:14:14;
[0127] 4. Mixing the polymer mixed solution and the initiator solution uniformly to obtain a mixed solution, wherein the mass ratio of the polymer mixed solution to the initiator solution is 70:29;
[0128] 5. Add 50 wt% of the mixed solution into the reactor at 75°C and react for 0.5 h to obtain the first reactant;
[0129] 6. Add the remaining mixed solution to the first reactant at a uniform speed, and control the uniform speed addition time to be completed for 1 hour, and then react at 75°C until the viscosity of the reactant reaches 50000mPa·s, stop the reaction, evaporate the solvent, and obtain the main glue;
[0130] 7. Evenly mix the castor oil-based polyurethane prepolymer, the main glue, pentaerythritol triacrylate and ethyl acetate in a mass ratio of 100:100:20:80 to obtain a UV glue;
[0131] The other operations are the same as those in Example 1.
[0132] The UV adhesive prepared in Examples 1-6 and Comparative Examples 1-3 and 7 is made into a UV adhesive film, comprising the following steps:
[0133] Step 1, uniformly mixing the above UV glue and ethyl acetate to obtain a UV glue solution with a solid content of 45%-55%;
[0134] Step 2, coating the UV adhesive solution onto a polyolefin base film layer with a thickness of 100 μm, and drying to obtain a composite layer, wherein the thickness of the UV adhesive layer is 30 μm;
[0135] Step 3: irradiate the composite layer with low UV light, then attach a polyester release film layer with a thickness of 20 μm, and age it to obtain a UV adhesive film.
[0136] The UV adhesive prepared in Comparative Example 8 is made into a UV adhesive film, comprising the following steps:
[0137] Step 1, mixing the above UV glue and ethyl acetate evenly to obtain a UV glue solution with a solid content of 45%-55%;
[0138] Step 2, coating the UV adhesive solution onto a polyolefin base film layer with a thickness of 100 μm, and drying to obtain a composite layer, wherein the thickness of the UV adhesive layer is 30 μm;
[0139] Step 3: irradiate the composite layer with low UV light, then attach a polyester release film layer with a thickness of 20 μm, and age it to obtain a UV adhesive film.
[0140] The 180° peel strength of the UV adhesives prepared in Examples 1-6 and Comparative Examples 1-3 and 7-8 was tested before UV irradiation. The UV adhesives in Examples 1-6 and Comparative Examples 1-3 and 7-8 were irradiated with UV having a wavelength of 365 nm. The controlled dose in Examples 1-4 and Comparative Examples 1-3 and 7-8 was 25 mJ / cm 2 In Example 5, the controlled dose is 10 mJ / cm 2 In Example 6, the controlled dose is 5 mJ / cm 2 , the 180° peel strength after low UV dose UV irradiation was tested; the UV adhesives of Examples 1-6 and Comparative Examples 1-3, 7-8 were irradiated with UV having a wavelength of 365 nm, wherein the controlled dose of Examples 1-6 and Comparative Examples 1-3, 7 was 40000 mJ / cm 2 , the controlled dose of comparative example 8 is 8000mJ / cm 2 , test the 180° peel strength after high UV dose UV irradiation; calculate the number average molecular weight of UV glue and calculate the water contact angle;
[0141] Among them, the 180° peel strength is tested according to the GB / T2792-2014 method;
[0142] The method for detecting the number average molecular weight includes the following: using tetrahydrofuran as an eluent, using a gel permeation chromatograph (Waters1515) to test the molecular weight of the UV glue (test temperature is 25°C, flow rate is 1 mL / min), and using a polystyrene standard sample as a standard curve to determine the number average molecular weight of the sample;
[0143] The water contact angle detection method includes the following: sticking a UV adhesive film on the wafer surface, peeling off the film after UV curing, and using the Theta Flex contact angle meter to test the water contact angle of the wafer surface;
[0144] The specific test results are shown in Table 1:
[0145] Table 1
[0146]
[0147]
[0148]
[0149] Before UV irradiation, the UV adhesive provided by the embodiment of the present invention has a 180° peel strength of 20N / 25mm-40N / 25mm. After low UV dose (5mJ / cm 2 -30mJ / cm 2 ) irradiation, UV adhesive can achieve adhesion enhancement effect, 180° peel strength can be increased to 26N / 25mm-43N / 25mm; after high UV dose (30000mJ / cm 2 -40000mJ / cm 2 ) after irradiation, the crosslinking degree of the UV glue polymer is greatly increased, achieving a viscosity reduction effect, and the 180° peel strength can be reduced to 0.12N / 25mm-0.35N / 25mm. In addition, the water contact angle of the substrate after peeling off the UV glue can be as low as 74.71°, which is close to the water contact angle of the blank substrate (72.68°). The UV glue provided by the present invention also has an extremely low amount of residual glue.
[0150] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A UV glue, characterized in that: The invention comprises the following raw material components in parts by weight: 43-47 parts of isooctyl acrylate, 10-13 parts of butyl acrylate, 2-3 parts of hydroxyethyl acrylate, 4-5 parts of methyl methacrylate, 1-2 parts of acrylic acid, 2-4 parts of benzophenone monomers and 1-7 parts of tris(trimethylsiloxy)silyl monomers; Wherein, the molecular weight of the benzophenone monomer is 200-300; The molecular weight of the tris(trimethylsiloxy)silyl monomer is 370-470.
2. The UV glue according to claim 1, characterized in that: The benzophenone monomer is 4-acryloxybenzophenone; and / or The tris(trimethylsiloxy)silane-based monomer is 3-methacryloxypropyl tris(trimethylsiloxy)silane.
3. A method for preparing the UV adhesive according to any one of claims 1 to 2, characterized in that: The steps include: S1, isooctyl acrylate, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, acrylic acid, benzophenone monomers and tris(trimethylsiloxy)silyl monomers are mixed uniformly to obtain a polymer mixed solution; S2, mixing benzoyl peroxide, anhydrous ethanol and ethyl acetate uniformly to obtain an initiator solution; S3, mixing the polymer mixed solution and the initiator solution uniformly to obtain a mixed solution; S4, reacting 33wt%-50wt% of the total amount of the mixed solution at 73° C.-76° C. to obtain a first reactant; S5. Add the remaining mixed solution to the first reactant, and then react at 73° C.-76° C. to obtain UV glue.
4. The method for preparing UV glue according to claim 3, characterized in that: In S2, the mass ratio of benzoyl peroxide, anhydrous ethanol and ethyl acetate is (1-2):(13-15):(13-15).
5. The method for preparing UV glue according to claim 3, characterized in that: In S3, the mass ratio of the polymer mixed solution to the initiator solution is (70-73):(27-32).
6. The method for preparing UV glue according to claim 3, characterized in that: In S4, the reaction time is 0.5h-1h.
7. The method for preparing UV adhesive according to claim 3, characterized in that: In S5, the remaining mixed solution is added dropwise at a uniform speed for a time of 0.5 h to 1 h.
8. The method for preparing UV adhesive according to claim 3, characterized in that: In S5, the condition for the reaction to end is: the viscosity of the reactants is 50000 mPa·s-200000 mPa·s.
9. A UV adhesive film, characterized in that: It includes a base film layer, a UV adhesive layer and a release film layer stacked in sequence; The UV adhesive layer is prepared from the UV adhesive described in any one of claims 1-2.
10. A method for preparing the UV adhesive film according to claim 9, comprising the following steps: Step 1, mixing the UV glue and ethyl acetate evenly to obtain a UV glue solution with a solid content of 45%-55%; Step 2, coating the UV adhesive solution on the base film layer and drying to obtain a composite layer; Step 3: UV irradiate the composite layer, attach a release film layer, and age it to obtain a UV adhesive film.
Citation Information
Patent Citations
UV light-induced peelable adhesive and preparation method thereof
CN114672276A
High-performance OCA (Optical Clear Adhesive) for bonding curved screen and preparation method of high-performance OCA
CN117820981A
Solvent-free light-cured organosilicone acrylate polymer pressure-sensitive adhesive and preparation method thereof
CN118546290A
Preparation method of organic silicon hybridized acrylate pressure-sensitive glue and pressure-sensitive adhesive tape
CN119242223A
Ultraviolet-ray-crosslinkable type acrylic-based pressure-sensitive adhesive
JP2006144014A